Antesenden Keputusan Pembelian Produk UMKM Kota Pontianak Melalui Aplikasi Shopee - Dina Octaviani; Rianti Ardana Reswari; Cesy Iola Kariza (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The utilization of e-commerce as a marketplace provides opportunities for Micro, Small and Medium Enterprises (MSMEs) because it facilitates transactions and develops businesses through technological innovation. This research offers a perspective on MSME products to use e-commerce as a sales medium by paying attention to programs on discounts and promotions in shaping consumer confidence to lead to purchasing decisions on MSME products. All hypotheses are significantly accepted by showing the results that promotion through the Shopee application can dominantly influence purchasing decisions for products offered by MSME players in Pontianak City. Marketing content management is recommended to market MSME products on the Shopee application.